The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1016/s0168-6496(98)00071-3
|View full text |Cite
|
Sign up to set email alerts
|

Colonisation and transmission of lux-marked and wild-type Aeromonas salmonicida strains in Atlantic salmon (Salmo salar L.)

Abstract: Colonisation and transmission of Aeromonas salmonicida in Atlantic salmon was investigated using wild-type and luxmarked strains of A. salmonicida. An initial intra-peritoneal (i.p.) challenge showed that lux-marked cells were virulent only when injected at concentrations v10 W cfu ml 3I and significantly less infective than wild-type MT463. The low virulence of A. salmonicida MT463 luxAB was probably due to loss of the proteinaceous A-layer, which is an important virulence factor involved in both intra-and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…In fish, Aeromonas salmonicida expressing luxAB was used to monitor colonization and transmission of the pathogen in Atlantic salmon ( Salmo salar ), but bioluminescence was not detected in live fish (Ferguson et al , 1998). In addition, luxAB marked A. salmonicida required exogenous addition of aldehyde substrate for luminescence (Ferguson et al , 1998). We have previously used luminescent E. ictaluri ( luxCDABE carried on a ColE1 plasmid) for in vitro quantification of E. ictaluri serum resistance (Lawrence et al , 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fish, Aeromonas salmonicida expressing luxAB was used to monitor colonization and transmission of the pathogen in Atlantic salmon ( Salmo salar ), but bioluminescence was not detected in live fish (Ferguson et al , 1998). In addition, luxAB marked A. salmonicida required exogenous addition of aldehyde substrate for luminescence (Ferguson et al , 1998). We have previously used luminescent E. ictaluri ( luxCDABE carried on a ColE1 plasmid) for in vitro quantification of E. ictaluri serum resistance (Lawrence et al , 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Real-time monitoring of bacterial infection using BLI in a living host has been used mainly in mouse models (Contag et al, 1995;Forde et al, 1998). In fish, Aeromonas salmonicida expressing luxAB was used to monitor colonization and transmission of the pathogen in Atlantic salmon (Salmo salar), but bioluminescence was not detected in live fish (Ferguson et al, 1998). In addition, luxAB marked A. salmonicida required exogenous addition of aldehyde substrate for luminescence (Ferguson et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that skin, lateral line, gills and GI tract (or a combination of these organs) are infection routes for pathogenic bacteria. In a study on Atlantic salmon Salmo salar L., Ferguson, Bricknell, Glover, MacGregor & Prosser (1998) suggested that the gills and skin/mucus regions were the main sites for attachment of A. salmonicida. Here, we have clearly demonstrated that A. salmonicida ssp.…”
Section: Discussionmentioning
confidence: 99%
“…However, as demonstrated earlier in this study, Digestarom ® has a direct antimicrobial effect, and because it was delivered as a feed supplement it seems likely that this effect would be most efficient within the digestive track. A. salmonicida, on the other hand, can infect the fish through the intestine (Jutfelt et al 2006), gills or epithelium (Svendsen & Bøgwald 1997, Ferguson et al 1998. Therefore, the antimicrobial effect of Digestarom ® is likely to play an important protective role in fish exposed through natural routes of exposure, whereas injecting the bacterial solution intraperitoneally would bypass this protective effect.…”
Section: In Vivo Challenges With Aeromonas Salmonicidamentioning
confidence: 99%